2017
DOI: 10.1097/md.0000000000008745
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism of rs266729 in adiponectin gene and type 2 diabetes mellitus

Abstract: Genome-wide association studies and meta-analyses indicate that the polymorphism of rs266729 in adiponectin gene increases the risk of type 2 diabetes mellitus (T2DM); however, these study methods have not been able to identify the underlying genetic effect on the development of T2DM. A genetic model-free approach was conducted to determine the underlying genetic model of inheritance of T2DM because of rs266729 in adiponectin gene.We searched available studies on the association between the rs266729 in adipone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…This was demonstrated because subjects with GG genotype in rs266729 exhibited higher plasma adiponectin levels than those of other genotypes in some replicated studies, including those hailing from different ethnic backgrounds ( 40 , 41 ). This SNP is supposed to be the most promising genetic variation related to adiponectin level and also the risk of MS ( 42 ), T2DM ( 43 ), and insulin resistance ( 41 ). Another SNP located in the promoter region of ADIPOQ , rs1656930, was highly connected with the adiponectin levels of elderly Japanese subjects ( 44 ).…”
Section: Genetic Determinants Of Circulating Adiponectin Levelsmentioning
confidence: 99%
“…This was demonstrated because subjects with GG genotype in rs266729 exhibited higher plasma adiponectin levels than those of other genotypes in some replicated studies, including those hailing from different ethnic backgrounds ( 40 , 41 ). This SNP is supposed to be the most promising genetic variation related to adiponectin level and also the risk of MS ( 42 ), T2DM ( 43 ), and insulin resistance ( 41 ). Another SNP located in the promoter region of ADIPOQ , rs1656930, was highly connected with the adiponectin levels of elderly Japanese subjects ( 44 ).…”
Section: Genetic Determinants Of Circulating Adiponectin Levelsmentioning
confidence: 99%
“…Whereas, the results of a meta-analysis suggested that SNP + 45 G allele might be a susceptibility allele for T2DM in the population, as elaborated by Li and Li [46]. In another meta-analysis report, the results indicated the susceptibility of obesity as a function of adiponectin gene polymorphism [47].…”
Section: Highlightsmentioning
confidence: 92%
“…Recent years, adiponectin ( APM1 ) gene has been widely studied in type 2 DM (T2DM) [ 16 – 19 ] . The APM1 gene was located in the chromosomal region at 3q27, and was responsible for encoding adiponectin.…”
Section: Introductionmentioning
confidence: 99%